Remote Virus Disinfection System: A Case Study in a Developing Country - Avilés-Castillo, Fátima (2023)
Germs and viruses are present on all surface's humans touch, including their clothing and bodies. Homeless people are highly predisposed to carry these viruses and suffer from diseases. This motivated the development of the present study that describes the design of a control system for a disinfection booth. Low-cost components were used, which can be acquired locally and maintain the physical characteristics of the existing booth, which was donated by the community. The Arduino Uno embedded board, and the NodeMCU board for remote control were used as the processing unit. The data acquisition element is an infrared presence sensor that detects when a person enters the cabin. This also controls the spraying of the disinfectant liquid automatically. The operation of this mechanism provides continuous and stable spraying, whose ignition can be controlled from a mobile application through a local network. Experimental tests show that implementing five nebulizers allows a high percentage of disinfectant coverage. A usability test (SUS) was also applied, offering 81% acceptance, which validated its use and allowed receiving feedback to improve this prototype.